Additional Benefits of Facial Nerve Monitoring during Otologic Surgery. (September 2020) - Casano, Kelsey; Giangrosso, Gerard; Mankekar, Gauri; Sevy, Alexander; Mehta, Rahul; Arriaga, Moises
Objective: This study assesses the role of facial nerve monitoring (FNM) for intraoperative decision making during otologic surgery and possible benefits beyond protecting facial nerve integrity. Study Design: This prospective study examines intraoperative FNM data and structured interviews collected during 52 otologic procedures. Setting: Tertiary referral center. Subjects and Methods: Subjects include adults and children undergoing middle ear or mastoid surgery. Data include intraoperative neuromonitoring activity and structured interviews conducted with the operating surgeon immediately following surgery. Results: Facial nerve stimulation was used to confirm the position of the nerve in 42 of 52 surgical procedures. In 26.9% of cases, the patient became "light" and moved under anesthesia, which was predicted by neuromonitoring 71.4% of the time. Through structured interviews, the operating surgeons reported the following. (1) The facial nerve took an unexpected anatomic course in 7.8% of patients and was difficult to identify in 39.2%. (2) The nerve was at increased risk of injury in 66.7% of cases due to chronic disease or previous surgery. (3) Among these high-risk cases, the monitor helped reduce the risk of nerve damage 100% of the time. (4) Neuromonitoring allowed the surgeon to operate faster 86.5% of the time, and (5) FNM allowed the resident to perform more of the operation 68.9% of the time. No patients experienced postoperative facial weakness. Conclusions: Beyond potentially protecting facial nerve integrity, this study identified additional benefits of FNM, including warning of patient movement during anesthesia, confirming facial nerve anatomic location, reducing operative time, and enhancing resident surgical experience.